2009
DOI: 10.1063/1.3138762
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mechanical theory for non-equilibrium systems. IX. Stochastic molecular dynamics

Abstract: The general form for the probability density and for the transition probability of a nonequilibrium system is given. Maximization of the latter gives a generalized fluctuation-dissipation theorem by providing a molecular basis for Langevin's friction force that avoids continuum hydrodynamics. The result shows that the friction coefficient must be proportional to the variance of the stochastic equations of motion. Setting the variance to zero but keeping the friction coefficient nonzero reduces the theory to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…By virtue of the fluctuation-dissipation theorem derived by Langevin, the friction coefficient must be proportional to the stochastic force variance, which controls the temperature fluctuations. 76 As expected, a friction coefficient of 2.0 ps −1 provides balanced temperature coupling without the dampening effect on the dynamics associated with larger values. Our results are in good agreement with the findings of Paterlini and Ferguson 63 which demonstrated that γ in the range of 1 to 5 ps −1 is an optimum parameter for Langevin dynamics simulations in water.…”
Section: Discussionsupporting
confidence: 70%
“…By virtue of the fluctuation-dissipation theorem derived by Langevin, the friction coefficient must be proportional to the stochastic force variance, which controls the temperature fluctuations. 76 As expected, a friction coefficient of 2.0 ps −1 provides balanced temperature coupling without the dampening effect on the dynamics associated with larger values. Our results are in good agreement with the findings of Paterlini and Ferguson 63 which demonstrated that γ in the range of 1 to 5 ps −1 is an optimum parameter for Langevin dynamics simulations in water.…”
Section: Discussionsupporting
confidence: 70%
“…To sum up, even a brief review of the most recent literature devoted to thermodynamics and statistical physics clearly shows that we are currently confronted with a gaily coloured mixture of real concepts and traditional misconceptions -see, for example, the materials of the AIP conference entitled 'QUANTUM LIMITS TO THE SECOND LAW' [216], as well as the accompanying volume of the journal 'Entropy' containing a number of more detailed reports from that conference [217]. Meanwhile, it is truly inspiring to read serious, thoughtful work trying to overcome the persistent difficulties of the conventional thermodynamics and statistical physics [218][219][220][221]. In view of this, an attentive work with elder literature is indispensable: For sometimes we might come to the true treasuries of thoughts and notices, like the books by Prof. Dr. Peter Boas Freuchen (1866Freuchen ( -1959 [222,223].…”
Section: The Modern Trends and Conclusionmentioning
confidence: 99%
“…The claim is that the theory is completely general and encompasses all nonequilibrium systems, and a deal of quantitative evidence in support of the claim has been presented. [2][3][4][5] The theory to date has been tested for nonequilibrium phenomena for which the answer is already known from existing thermodynamic or statistical mechanical approaches. This paper addresses a class of nonequilibrium problems for which there is no accepted general theory, namely, the problem of nonequilibrium phases and the transitions between them.…”
Section: Introductionmentioning
confidence: 99%